Evolutionary Transitions to Multicellular Life: Principles and mechanisms - Trillo, Inaki Ruiz (Springer, 2015)
The book integrates our understanding of the factors and processes underlying the evolution of multicellularity by providing several complementary perspectives (both theoretical and experimental) and using examples from various lineages in which multicellularity evolved. Recent years marked an increased interest in understanding how and why these transitions occurred, and data from various fields are providing new insights into the forces driving the several independent transitions to multicellular life as well as into the genetic and molecular basis for the evolution of this phenotype. The ultimate goal of this book is to facilitate the identification of general and unifying principles and mechanisms.